Le diagnostic de l'exclusion professionnelle: comparaison des résultats obtenus à l'aide de deux instruments - Limoges, Jacques; Guédon, Marie-Chantal (Canadian Journal of Counselling and Psychotherapy, 2007)
Exclusion from work has economic, psychological and social impacts. Specific diagnosis of the difficulties encountered by people seeking employment can help to lessen these impacts by enabling counsellors to provide help for each person according to his or her specific needs. This article describes two diagnostic tools, software and an interview protocol, that were tested with the same job seekers. The main test results are given and are correlated for each diagnostic tool.